2022
DOI: 10.1107/s205698902200603x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and Hirshfeld surface analysis of ethyl (3E)-5-(4-chlorophenyl)-3-{[(4-chlorophenyl)formamido]imino}-7-methyl-2H,3H,5H-[1,3]thiazolo[3,2-a]pyrimidine-6-carboxylate

Abstract: In the title molecule, C23H20Cl2N4O3S, the thiazole ring is planar while the pyrimidine unit fused to it adopts a screw-boat conformation. In the crystal, thick sheets parallel to the bc plane are formed by N—H...N, C—H...N and C—H...O hydrogen bonds together with π–π interactions between the formamido carbonyl groups and the thiazole rings. Hirshfeld surface analysis indicates that the most important contributions to the crystal packing are from H...H (30.9%), Cl...H/H...Cl (20.7%), C...H/H...C (16.8%) and O.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Data are average of a minimum of five fruits per treatment and evaluated statistically by the calculation of averages + standard deviation or ANOVA and mean separation by Duncan’s multiple range tests at the 5% level of significance. This work confirms that there are different applications for bioactive compounds in agriculture and other fields which is reflected in many papers that have been published before. Also, it is interesting to clarify that the importance of this paper and other agricultural research lies in their significant contribution in solving worldwide concerns, including food security, environmental sustainability, and economic development. …”
Section: Methodssupporting
confidence: 75%
“…Data are average of a minimum of five fruits per treatment and evaluated statistically by the calculation of averages + standard deviation or ANOVA and mean separation by Duncan’s multiple range tests at the 5% level of significance. This work confirms that there are different applications for bioactive compounds in agriculture and other fields which is reflected in many papers that have been published before. Also, it is interesting to clarify that the importance of this paper and other agricultural research lies in their significant contribution in solving worldwide concerns, including food security, environmental sustainability, and economic development. …”
Section: Methodssupporting
confidence: 75%
“…This work confirms the high importance of organic molecules due to their various applications as reported before. [22][23][24][25][26][27]…”
Section: Discussionmentioning
confidence: 99%
“…4,5,6 Sorption has major effects on the physical accessibility of microorganisms to the pollutant and plays a significant role in the pollutant's mobility. 7,8 Acidic herbicides exist as either anions or neutral molecules depending upon whether the soil solution pH is below or above the pKa. Theoretically, anionic, and neutral forms will be present in equal amounts when the pH is equal to the pKa.…”
Section: Introductionmentioning
confidence: 99%
“…10 One of the main environmental factors that influence adsorption of organic compounds in soil is the temperature. 7,11 It is often assumed that adsorption is an exothermic process, whereby an increase in temperature leads to decreased adsorption and increased desorption rates. 12,13 However, thermodynamic studies have shown a highly variable relationship to temperature due to the complexicity of the soil environment.…”
Section: Introductionmentioning
confidence: 99%